2019
DOI: 10.2147/jmdh.s233614
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge, Beliefs, and Attitudes Concerning Genetic Testing Among Young Jordanians</p>

Abstract: BackgroundMedical genetic testing is an evolving side of clinical care that helps people to make informed medical and lifestyle decisions. The source of knowledge, personal beliefs, and attitude towards genetic testing are the main determinative factors of getting optimal utilization of such technology in reducing/prevention of diseases.MethodsA structured survey was used to assess the knowledge, beliefs, and attitude regarding genetic testing among 463 young adults aged 18 years or older living in the North o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…This finding can be attributed to the increased reporting of genetic testing in recent years in Malaysia (Yoon et al, 2011;Balasopoulou et al, 2017), which resulted in greater public familiarity of the topic of genetic testing for hereditary disorders. Similar results were observed in some countries in the Middle East, where majority of respondents in Jordan had heard of genetic testing (Mohammad Bagher et al, 2019), while most northern Iranians were interested in using genetic counseling services and genetic tests before marriage (Altaany et al, 2019).…”
Section: Knowledge Of Genetic Testing For Hereditary Disorderssupporting
confidence: 82%
See 2 more Smart Citations
“…This finding can be attributed to the increased reporting of genetic testing in recent years in Malaysia (Yoon et al, 2011;Balasopoulou et al, 2017), which resulted in greater public familiarity of the topic of genetic testing for hereditary disorders. Similar results were observed in some countries in the Middle East, where majority of respondents in Jordan had heard of genetic testing (Mohammad Bagher et al, 2019), while most northern Iranians were interested in using genetic counseling services and genetic tests before marriage (Altaany et al, 2019).…”
Section: Knowledge Of Genetic Testing For Hereditary Disorderssupporting
confidence: 82%
“…As reported in a previous study in New York city, ethnic and racial identities are associated with the perception of the benefits of and barriers to the application of genetic testing (Sussner et al, 2011 ). In addition, a study conducted in Jordan also revealed that 12% of the respondents believed that genetic tests were forbidden (Altaany et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This experience can positively affect a person's attitude toward genetic screening, primarily if the family refers to the doctor and gets examinations to perform diagnosis. Literature mentions that having a family member with inherited diseases will make another family more aware of screening approaches 26 Other people's experiences and opinions can be another factor that can influence the use of one's genetic screening, according to one component in the Theory of Planned Behavior 27 . Other people's opinions, especially doctors and other health workers, can help a non-expert understand complex genetic information and become an ideal source for making decisions about genetic screening 28 .…”
Section: Resultsmentioning
confidence: 99%
“…In this case, it is critical to assess the impact of PGS on society as the occurrence of diseases that are tested by PGS results in the need for long-term treatments and care, increases the use of health professionals, and gets access to medical equipment and medications. The genetic disease is regarded as a high burden on society, including the psychological benefit of PGS for at-risk individuals for a particular disease which they know from their own family is the reduction of anxiety [30, 31].…”
Section: Discussionmentioning
confidence: 99%